How Abusive Supervision Affects Job Performance- From Both Direct and Indirect Perspectives - Gao, Ming (Transactions on Economics, Business and Management Research, 2024)
Abusive supervision has received a great deal of attention since it was proposed by Tepper,and it has been shown to have complex effects on abused employees. Recently, scholars have begun to focus on abusive supervision as perceived by third parties to study the impact of this workplace abuse phenomena on a wider range of bystanders in the organization. As a negative leadership style, abusive supervision is in relation to job performance closely and widely, extending from the direct abused victims to the indirect perceived third parties. This paper will summarize the previous literature on the impact of abusive supervision on job performance from both direct and indirect perspectives.